Facility delivery and postnatal care services use among mothers who attended four or more antenatal care visits in Ethiopia: further analysis of the 2016 demographic and health survey - Gedefaw Abeje Fekadu; Fentie Ambaw; Seblewongiel Ayenalem Kidanie (BMC, 2019)
Abstract Background Antenatal care provides the best opportunity to promote maternal and child health services use. But many Ethiopian mothers deliver at home and fail to attend postnatal care. Therefore, this study was done to identify factors associated with health facility delivery among mothers who attended four or more antenatal care visits. The study was also intended to identify factors associated with postnatal care service use among mothers who delivered at home after four or more antenatal care visits. Methods This study used the 2016 Ethiopian Demographic and Health Survey data. Two thousand four hundred fifteen women who attended four or more antenatal care visits were included to identify factors associated with health facility delivery after four or more antenatal care visits. Among them, 1055 mothers delivered at home. These women were included to identify factors associated with postnatal care service use. Stata 15.1 was used to analyze the data. Multivariable logistic regression model was fitted to identify associations between the outcome and predictor variables. Results Among women who had four or more antenatal care visits, 56% delivered at health facility. Mothers with secondary or higher level of education (AOR = 2.9; 95% CI = 1.6-5.3), urban residents (AOR = 3.4; 95% CI = 1.9-6.1), women with highest wealth quintile (AOR = 2.7; 95% CI = 1.5-4.8), and working women (AOR = 1.6; 95% CI = 1.2-2.3) had higher odds of delivering at health facilities. High birth order (AOR = 0.5; 95% CI = 0.3-0.7) was negatively associated with a lower likelihood of health facility delivery. Among women who delivered at home, only 8% received postnatal care within 42 days after delivery. Only the content of care received during antenatal care visits (AOR = 1.40; 95% CI = 1.1-1.8) was significantly associated with postnatal care attendance. Conclusion Women with lower socio-economic status had lower odds of giving birth at health facility even after attending antenatal care. The more antenatal care components a mother received, the higher her probability of delivering at health facility. Similarly, postnatal care attendance was higher among women who had received more antenatal care components.